Morada - Pasin, Camila Calvo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This Experimental Project is a photojournalism book of urban inequality, focusing on the issue of housing, which stands as one of the main pillars of the issues placed on the agenda. Thus, we address different aspects that concern the discussion, as the struggle of families and social movements for habitation, the discrepancy between the different forms of housing inserted in the same geographical context - which illustrates the contrast between wealth and poverty - life conditions in marginalized regions, homelessness and even the urban setting exodus to the struggle for land. The objectives of this study were to report, through the photographic language, social inequality in the urban context, as well as refine the knowledge about the problem, proving the argumentative capacity of photography as ideological message transmission. Therefore, we use as methodology the previous study for theoretical background on the subject, substantiated by the scientific research carried out previously, the use of such language picture to engender the narrative and social denunciation addition to humanize the product, and the use of texts reinforce the critical reflection on the issue. As a result, we present social inequalities through the images represented in photojournalism

Este Projeto Experimental é um livro de fotorreportagem sobre a desigualdade urbana, com enfoque na questão da moradia, que se firma como um dos principais pilares da problemática colocada em pauta. Dessa forma, abordamos diferentes aspectos que tangem à discussão, como a luta de famílias e movimentos sociais por moradia, a discrepância entre as diferentes formas de habitações inseridas no mesmo contexto geográfico - que ilustra o contraste entre a riqueza e pobreza -, as condições de vida em regiões marginalizadas, a falta de moradia e, até mesmo, o êxodo do cenário urbano para a luta rural por terras. Os objetivos desse trabalho foram denunciar, por meio da linguagem fotográfica, a desigualdade social no contexto urbano, além de sensibilizar o leitor acerca da problemática, comprovando, assim, a capacidade argumentativa da fotografia como transmissão de mensagem ideológica. Para tanto, utilizamos como metodologia o estudo prévio para embasamento teórico sobre o tema, substanciado pela pesquisa de iniciação científica desenvolvida anteriormente, o uso da fotografia como linguagem para engendrar a narrativa e denúncia social além de humanizar o produto, e o uso de textos que reforçam a reflexão crítica acerca da questão. Como resultado, apresentamos as desigualdades sociais por meio das imagens representadas na fotorreportagem
Keywords: Urbanização; Fotojornalismo; Habitações; Igualdade; Fotografia paisagistica; Urbanization